War and Democracy - Gregory D. Hess; Athanasios Orphanides (Center for Economic Studies and ifo Institute (CESifo), 1999)
This paper presents a general equilibrium model of conflict based on a world populated by representative democracies. At the individual state level, when information regarding a leader's ability to defend the state against unavoidable conflict is va luable to voters, an incumbent leader seeking reelection may be tempted into potentially avoidable conflicts to demonstrate his ability and enhance his reelection prospects. As a result, democratic states may be responsible for at least some international conflict. In this paper, we investigate whether this motive is sufficiently important for war to persist in equilibrium if all countries are democracies. Three key findings emerge. First, the perpetual peace equilibrium hypothesized by Immanuel Kant (1795, 1991) always exists. The reason is that in the absence of the threat of war, leaders are unable to divert the public's attention away from domestic considerations. Consequently, the incentive for potentially avoidable conflicts vanishes. Second, if leader s are not sufficiently benevolent and wars are costly in expectation, then additional equilibria exist with a positive war frequency. Third, if multiple equilibria exist, the perpetual peace equilibrium may be unstable in which case an equilibrium with po sitive war frequency becomes the only stable outcome. The model is further extended to analyze the role of appropriative conflicts and non-democratic regimes. It is shown that if the diversionary motive of democratic leaders is strong, a more democratic world may not necessarily be more peaceful. We discuss the role that norms and institutions can play in facilitating a more peaceful world with democracies - for example, free trade areas and alliance formation.
Keywords: 330; War; Democracy; Kant Hypothesis